A survey of cranberry fruit rots in commercial production beds in Oregon and Washington - Valentine, Don C.; Bouska, Cassie; Stockwell, Virginia O. (Frontiers in Plant Science, 2024)
Fungal fruit rots are a perennial threat to the production of cranberries. Eleven genera of fungi have been reported to cause cranberry rot in the field and/or during cold storage. Oregon and Washington rank fourth and fifth in the production of cranberries in the USA, but much of the research on cranberry fruit rots has been conducted in Wisconsin, New Jersey, and Massachusetts. A survey of fungal fruit rot pathogens was conducted over four years in commercial cranberry farms located in the Pacific Ocean coastal zone in Oregon and Washington. Yield, rot incidence, and fungal pathogens isolated varied year-to-year. Pathogens isolated frequently from field-rotted cranberries included the cranberry fruit rot genera described in other cranberry production regions of the USA, such as Colletotrichum, Coleophoma, and Physalospora. Neofabraea actinidiae, a recently described cranberry fruit rot, was isolated consistently from field-rotted cranberries from beds with specific fungicide usage patterns. N. actinidiae also was one of the more common storage rot pathogens in this region, alongside other well-established storage rots like Coleophoma and black rots caused by Allantophomopsis cytisporea, A. lycopodina, and Strasseria geniculata. This may have important implications for Washington cranberry production because a large proportion of the crop is dryharvested, placed in cold storage, and then sold as fresh cranberries. Climatic differences among the cranberry production areas across the United States may affect the disease incidence and prevalence of different genera of cranberry fruit rot pathogens, as summer months in Oregon and Washington are often much cooler and dryer than in Wisconsin and east coast states and may account for differing presence of various cranberry fruit rot fungi.